FRAMING PEMBERITAAN RANCANGAN UNDANG-UNDANG PENGHAPUSAN KEKERASAN SEKSUAL PADA MEDIA TIRTO ID DAN REPUBLIKA CO ID - Akbar, Adrial (Master of Communication Science Program, Universitas Diponegoro, 2021)
In the middle of increasing concerns about acts of sexual violence, the Draft Law on the Elimination of Sexual Violence (RUU PKS), has not yet been ratified. It is made worse by many people who refuse the approval due to the circulation of misinformation. And the press plays an important role here. It can be a corrector or even a disseminator of misinformation, depending on the framing that is formed. Therefore, this study explains the framing patterns of republika.co.id and tirto.id in presenting news related to the RUU PKS. The research method used is Pan and Kosicki model framing analysis. The researcher looks for the reality that the two media want to build by analyzing the news that is spread around the RUU PKS using four structures, namely: syntax, script, thematic and rhetorical. And it was found that republika.co.id had a framing that the RUU PKS. was not ready to be ratified because many parties, both in general and from the Indonesian House of Representatives itself, thought that this bill could not be ratified. Meanwhile, tirto.id has framing to describe the lack of seriousness of the Indonesian House of Representatives in discussing the RUU PKS, which led to the failure of this bill to be passed, as well as trying to correct the misinformation circulating. Therefore, the two media analyzed have different framing in presenting news related to the RUU PKS.